REKAYASA PEMBUATAN MESIN PERAJANG RUMPUT UNTUK KELOMPOK PETERNAK SAPI DI KABUPATEN SLEMAN DAN BANTUL MENGGUNAKAN PROGRAM APLIKASI AUTOCAD - Joko Waluyo; Yuli Pratiwi; Imam Sodikin (JURNAL GAUNG INFORMATIKA, 2016)
Cattle Breeders Group Kandang Sedyo Makmur in Dukuh Ngemplak, Desa Umbul Martani, Kecamatan Ngemplak Kabupaten Sleman, raising 250 cattle with 10 tons / day feed requirement, and dan Cattle Breeders Group Catur Andini in Dukuh Wonocatur, Desa Banguntapan Kabupaten Bantul, raising 80 cows with 3.2 tons / day feed requirement. Problems that exist in these two groups of cattle ranchers is during the rainy season grass needs can be met and excessive amount of grass supplies, while during the dry season grass supplies are still less consequent needs of the grass can not be fulfilled.Based on the above, it is necessary to engineer the grass chopper machine to optimize the animal feed which during the rainy season is abundant to be cut, processed and stored and can be used for animal feed needs during the dry season. This machine is also able to cut corn stems and stems of sugar cane crops so that it can be used as animal feed, especially to increase the supply of animal feed in the dry season so that the needs of animal feed can be met. Because based on the facts on the ground, cutting corn stalks of corn and sugarcane are quite hard, can not be done manually with a cutting tool like a sickle. The working principle of grass chopper machine is corn stalk, stalk of sugar cane and straw and elephant grass inserted at entrance at tool, then cutting tool rotate and directly cut the stem of plant that has been entered, so happened cutting process, then result of cutting out through the exit of the machine that has been prepared bagor bag so that pieces can go directly into the bag so it is not scattered. This activity can be realized because of obtaining grant for Science and Technology for Society financed by Kemenristek Dikti. Based on the results of grass cutter machine testing, it was able to cut the grass elephant, corn stalks and sugar cane as much as 10 kg / menit or 600 kg / hour with homogeneous pieces and small size, whereas if done manually using human labor with tools cut the sickle, it was only able to cut as much as 1kg / minute with the cutout results are not homogeneous. By making grass chopper machine,sugarcane stalk and corn stalk, it can reduce the need for labor so that operational costs can be reduced and the income of the cattle breeder group can increase.